Etude d'évolution de l'envasement dans le barrage de Foum El Gherza –Biskra- - داود, قرح; عبد العزيز, بكوشة (University of El-Oued, 2020)
The réservoir of the Foum El Gherza dam is subjectif to heavy sédimentation due to the érosion of the water shed. Thus, a cumulative 32 million m³ was deposited From 1950 to 2004 since then reducing its capacity to less than 50%. Based on bathymetric surveys carried out by the National Dams Agency on the dam reservoir. The dredging opérations carried out made it possible to remove approximately 18.82 million cubic meters. However, the situation, phénoménaux incérasses, which calls for continuity of the dredging process and réduce the pيتعرض خزان سد فم الغرزه لترسيب كثيف بسبب تآكل مستجمعات المياه. وهكذا ، تم إيداع 32 مليون متر مكعب من عام 1950 إلى 2004 منذ ذلك الحين مما قلل من قدرتها إلى أقل من 50٪. بناءً على مسوحات قياس الأعماق التي أجرتها وكالة السدود الوطنية على خزان السد. مكنت عمليات التجريف التي تم إجراؤها من إزالة 18.82 مليون متر مكعب. ومع ذلك ، فإن ظاهرة الطمي في تزايد كبير، مما يستدعي الأمر الى استمرار عملية التجريف والتقليل من الضاهرة .
ovrage hydraulique مذكرة ماستر تخصص
Keywords: Dam - Foum El-Gherza - Siltation - Evolution - Reservoir; سد - فم الغرزه - ترسيب - تطور - خزان